From resistance to ’bricolage’: Forms of ’power to’ get active and create possibilities in multilingual organizations - Gaibrois, Claudine (Revista Internacional de Organizaciones, 2020)
This article investigates the underaddressed productive power effects of multilingualism in professional contexts. Instead of conceiving of power in terms of possession, competition or limitation, it focuses on 'power to' get active, seize opportunities, create possibilities, take responsibility, make decisions, and relate to others. Re-analyzing data from a case study conducted in Switzerland, it shows how employees discursively construct various forms of getting active and creating possibilities to counterbalance the challenging aspects of their multilingual work environment. As a result, it presents a typology of agency creation in multilingual organizations. Agency is conceptualized as breaking away from a given frame of action and as taking initiatives to transform it.